2019
DOI: 10.1200/jco.19.00799
|View full text |Cite
|
Sign up to set email alerts
|

ARCHES: A Randomized, Phase III Study of Androgen Deprivation Therapy With Enzalutamide or Placebo in Men With Metastatic Hormone-Sensitive Prostate Cancer

Abstract: PURPOSE Enzalutamide, a potent androgen-receptor inhibitor, has demonstrated significant benefits in metastatic and nonmetastatic castration-resistant prostate cancer. We evaluated the efficacy and safety of enzalutamide in metastatic hormone-sensitive prostate cancer (mHSPC). METHODS ARCHES (ClinicalTrials.gov identifier: NCT02677896 ) is a multinational, double-blind, phase III trial, wherein 1,150 men with mHSPC were randomly assigned 1:1 to enzalutamide (160 mg/day) or placebo, plus androgen deprivation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
629
3
30

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 759 publications
(751 citation statements)
references
References 32 publications
16
629
3
30
Order By: Relevance
“…As a result, the treatment landscape of mCRPC is complex and continues to focus primarily on the order/sequencing of therapies. For instance, recent trials demonstrated early treatment with Abiraterone or Enzalutamide in the hormone-sensitive state could be beneficial (1315). However, there is a diverse array of molecular drivers contributing to disease heterogeneity amongst mCRPC patients (16, 17), leading to variable response to current treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the treatment landscape of mCRPC is complex and continues to focus primarily on the order/sequencing of therapies. For instance, recent trials demonstrated early treatment with Abiraterone or Enzalutamide in the hormone-sensitive state could be beneficial (1315). However, there is a diverse array of molecular drivers contributing to disease heterogeneity amongst mCRPC patients (16, 17), leading to variable response to current treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The panel's recommendation was made irrespective of metastatic burden (86% consensus). Recent data from the ARCHES, ENZAMET, and TITAN studies suggest clinical benefit with enzalutamide and apalutamide in this setting as well 61–63 . US FDA approval for these agents in mHSPC is pending.…”
Section: Resultsmentioning
confidence: 99%
“…9 The panel felt that T levels should be ENZAMET, and TITAN studies suggest clinical benefit with enzalutamide and apalutamide in this setting as well. [61][62][63] US FDA approval for these agents in mHSPC is pending.…”
Section: The Role Of Adt In Salvage Therapymentioning
confidence: 99%
“…First, we have focused on genes that are already expressed in castration-resistant prostate cancer cell lines rather than those that have emerged because of treatment with enzalutamide. We have also only focused on castration-resistant prostate cancer treated with enzalutamide, as at the initiation of our studies, enzalutamide treatment was not yet approved in the metastatic hormone-sensitive setting [47]. In addition, our study has been limited to 5,043 genes that are involved in signal transduction and are drug targets, which has left out a considerable number of potential drivers, like transcription factors, that likely play an important role in enzalutamide resistance.…”
Section: Discussionmentioning
confidence: 99%